Polyamide material, polyamide composite rubber seal and preparation method thereof

Through the combination of polyamide material and semi-vulcanized rubber, the problem of poor toughness and deformation recovery in special plastics and rubber composite materials is solved, and the friction performance and shear resistance of the seal are significantly improved, forming high-performance polyamide composite rubber Seals.

CN116199878BActive Publication Date: 2025-01-03XIAN AEROSPACE PROPULSION INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310052432.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-02
Publication Date
2025-01-03
Estimated Expiration
2043-02-02

AI Technical Summary

Technical Problem

Special plastics and rubber composites have problems such as low toughness matching, poor stress deformation recovery, insufficient interface bonding and shear resistance, resulting in low friction performance of the seal.

Method used

Using the preparation method of polyamide materials, the trihalotrium triamide monomer, dihalotrium polyether diamide monomer and aromatic diphenol are added in alkaline polar solvents, and the dihalotrium containing tertiary amine structure is added. The amide monomer forms a polyamide material and is combined with the semi-vulcanized rubber by spin coating technology to form a polyamide composite rubber seal.

Benefits of technology

The thermal, mechanical and friction resistance of polyamide composite rubber seals is improved, the interface bonding force and shear resistance are enhanced, and the friction performance of the seals is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The present invention discloses a polyamide material, a polyamide composite rubber seal and a preparation method thereof, which are used to solve the problems that the toughness of special plastics is not high enough to match the rubber, the stress deformation recovery is poor, the interface bonding force and the shear resistance are poor. A preparation method of a polyamide material, dihalogenated polyether diamide monomer and aromatic diphenol are dehydrated in an alkaline polar solvent in the presence of a dehydrating agent and a catalyst; dihalogenated amide monomer and trihalogenated triamide monomer containing a tertiary amine structure are added to heat up the polymerization reaction, and the polyamide material is obtained by cooling down. The amide group containing a tertiary amine structure is introduced into the main chain of the polymer molecule, which greatly improves the interface bonding force with the rubber product; the dihalogenated polyether diamide group is introduced into the main chain of the polymer molecule, which enhances the flexibility of the polymer; the trihalogenated triamide group is introduced into the main chain of the polymer molecule, so that the polymer has the recoverability of stress deformation. At the same time, a preparation method of a polyamide composite rubber seal and the obtained seal are provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a polyamide material, a polyamide composite rubber seal and a preparation method thereof. Background Art

[0002] Motion seals involve friction. Generally, improving the sealing will increase the friction, which will reduce the movement ability and quality, and accelerate the wear of the seal. At present, the general engine seals are mainly made of EPDM rubber or nitrile rubber, which have excellent aging and corrosion resistance, but their friction performance needs to be improved. Compared with rubber, plastic has a lower friction coefficient, better barrier properties, and higher strength and hardness, so it is less likely to wear during the wear process. In order to improve the sealing performance of rubber seals, it is proposed to combine the advantages of high-performance special plastics and rubber to improve the friction and sealing performance of rubber. The patents that have been applied for include environmentally friendly SEBS thermoplastic elastomers and their modified products and polypropylene and polyolefin elastomers under the action of coupling agents to obtain sealing strip materials; thermoplastic elastomers and resins under the action of coupling agents to obtain rubber-plastic sealing materials with stable dimensions at high and low temperatures. However, the current combination of special plastics and rubber has many problems, such as the toughness of the special plastics is not highly matched with the rubber, the stress deformation recovery is poor, the interface bonding strength and shear resistance of the special plastics and rubber composites are poor, and there is no synthetic coating material that matches the rubber strain and a composite preparation method. Summary of the invention

[0003] The purpose of the present invention is to solve the problems that the toughness of special plastics is not highly matched with rubber, the stress deformation recovery is poor, the interface bonding force and the shear resistance are poor, and at the same time, a coating material matching the rubber strain and a composite preparation method are synthesized, and a polyamide material, a polyamide composite rubber seal and a preparation method thereof are provided.

[0004] In the first aspect, a method for preparing a polyamide material adopts the following technical solution:

[0005] A method for preparing a polyamide material comprises the following steps:

[0006] Step 1), preparation of trihalotriamide monomer:

[0007] The alkaline aqueous solution of diethylenetriamine is added dropwise to the organic solution of p-halobenzoyl halide to react, and the purified trihalotriamide monomer is obtained by distillation, washing and drying;

[0008] Step 2), polyamide material preparation:

[0009] The dihalogenated polyether diamide monomer and aromatic diphenol are subjected to a dehydration reaction in an alkaline polar solvent in the presence of a dehydrating agent and a catalyst; a dihalogenated amide monomer and a trihalogenated triamide monomer containing a tertiary amine structure are added to perform a polymerization reaction at a high temperature, and a polyamide material is obtained by cooling the temperature.

[0010] By adopting the above technical solution, an amide group containing a tertiary amine structure is introduced into the main chain of the polymer molecule, and the interfacial bonding force with the rubber product is greatly improved through intermolecular hydrogen bonds and charge interactions; a dihalogenated polyether diamide group is introduced into the main chain of the polymer molecule to enhance the flexibility of the polymer; and a trihalogenated triamide group is introduced into the main chain of the polymer molecule to make the polymer recoverable from stress deformation.

[0011] Preferably, the dihaloamide monomer containing a tertiary amine structure is:

[0012] a kind of;

[0013] The dihalogenated polyether diamide monomer is:

[0014]

[0015] Where y is 2, 5 or 33;

[0016] The trihalotriamide monomer is:

[0017]

[0018] The aromatic diphenol is:

[0019]

[0020] One of;

[0021] Wherein, X is F, Cl or Br.

[0022] Preferably, step 1), preparation of trihalotriamide monomer, comprises the following steps:

[0023] S1, 100-105 parts of diethylenetriamine, 120-130 parts of alkali, and 0.5-20 parts of surfactant are sequentially added into 2500-5000 parts of deionized water, and dissolved at room temperature to obtain a diethylenetriamine solution;

[0024] S2, 475-660 parts of p-halobenzoyl halide and 3000-5000 parts of organic solvent are uniformly mixed, diethylenetriamine solution is added dropwise, and the mixture is reacted at room temperature for 2-5 hours to obtain a trihalotriamide monomer solution;

[0025] S3, distilling and recovering the organic solvent in the trihalotriamide monomer solution, collecting the crude product, washing, removing the solvent, and drying to obtain the purified trihalotriamide monomer.

[0026] Step 2), preparation of polyamide material, comprising the following steps:

[0027] Q1, 10-300 parts of dihalogenated polyether diamide monomer, 0.5-20 parts of catalyst, 5-40 parts of dehydrating agent, 110-320 parts of aromatic diphenol, 80-300 parts of alkali and 1000-2000 parts of polar solvent are mixed evenly, and dehydrated at 130-190°C for 0.5-3h under nitrogen protection;

[0028] Q2, add 200-300 parts of dihaloamide monomer containing tertiary amine structure and 2-20 parts of trihalotriamide monomer obtained in step 1) to the solution obtained in the above Q1, react at 190-230° C. for 1-8 hours, and cool to 25-150° C. to obtain a polyamide material.

[0029] By adopting the above technical solution, the preparation method of trihalogenated triamide monomer can obtain trihalogenated triamide monomer products with high yield and high purity. In addition, the reaction conditions of the method are relatively loose, the adaptability is strong, and the operation is simple and convenient. In addition, the use of surfactants can increase the reaction rate and effectively improve the quality of the product.

[0030] The method for preparing polyamide materials has the advantages of strong controllability, high product quality and relatively loose reaction conditions. By controlling the reaction conditions and adding different monomers, polyamide materials with desired structures and properties can be prepared.

[0031] Preferably, in the step 1) of preparing the trihalotriamide monomer, the base is one of a hydroxide, a carbonate, and an organic amine;

[0032] The surfactant is one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, sodium benzene sulfonate, sodium alginate, polysorbate, dodecylphenol polyoxyethylene ether, sorbitan monooleate, and polyethylene glycol.

[0033] The organic solvent is one of acetone, low-carbon alcohols, methyl chloride, ethyl chloride, carbon disulfide, and chlorinated aromatic hydrocarbons.

[0034] Preferably, in the step 2) of preparing the polyamide material, the catalyst is an organic acid salt of lithium, sodium, potassium or zinc metal ions;

[0035] The dehydrating agent is one of toluene and xylene;

[0036] The base is one of hydroxide, carbonate and organic amine;

[0037] The polar solvent is a highly polar aprotic solvent containing oxygen, nitrogen and sulfur.

[0038] In the second aspect, a polyamide material adopts the following technical solution:

[0039] A polyamide material is prepared by any of the above-mentioned methods for preparing the polyamide material.

[0040] By adopting the above technical solution, the polyamide material has excellent thermal properties, processability, mechanical properties, corrosion resistance and aging resistance, as well as excellent friction resistance.

[0041] In a third aspect, a method for preparing a polyamide composite rubber seal adopts the following technical solution:

[0042] A method for preparing a polyamide composite rubber seal comprises the following steps:

[0043] Step 1), surface treatment of semi-vulcanized rubber: the semi-vulcanized rubber is cleaned with ethanol before use, and then treated with low-temperature plasma;

[0044] Step 2), preparation of polyamide composite rubber seal: the polyamide material prepared by any of the above-mentioned preparation methods of the polyamide material is evenly coated on the surface of the semi-vulcanized rubber by means of rotary coating, and phase conversion is carried out in a phase conversion agent. After the gel reaction is completed, the solvent is purified to remove the residual solvent and by-product salt, and the polyamide composite rubber seal is obtained by molding after drying.

[0045] By adopting the above technical solution, the preparation method of the polyamide composite rubber seal has low preparation cost, strong controllability and good surface contact; after the surface of the semi-vulcanized rubber is treated with low-temperature plasma, the surface properties of the rubber can be effectively improved, so that the rubber has better surface adhesion. In addition, the polyamide material is coated by spin coating, which can ensure the uniformity of the coating and improve the adhesion of the coating.

[0046] Preferably, the low-temperature plasma treatment time is 2-60s, the treatment power is 20-100w, and the treatment temperature is 25-100°C;

[0047] During the coating, the coating thickness is controlled to be 70-200 μm;

[0048] The phase conversion agent is any one of deionized water, low-carbon alcohol aqueous solution, acetone aqueous solution, NMP aqueous solution, DMF aqueous solution, DMAc aqueous solution, and DMI aqueous solution;

[0049] During the molding process, the molding temperature is 100-280°C, the molding pressure is 1-10MPa, and the molding time is 2-30min;

[0050] The purification solvent is one of deionized water and low-carbon alcohol.

[0051] In a fourth aspect, a polyamide composite rubber seal adopts the following technical solution:

[0052] A polyamide composite rubber seal is prepared by using any of the above-mentioned preparation methods for the polyamide composite rubber seal.

[0053] By adopting the above-mentioned technical scheme, the polyamide composite rubber seal obtained by the preparation method of the polyamide composite rubber seal has matching deformation parameters of the polyamide material and the rubber material, good stress-deformation recoverability, and excellent properties such as strong surface bonding force and shear resistance, thereby improving and solving the defects of the traditional rubber and rubber-plastic composite material seals such as weak friction resistance. DETAILED DESCRIPTION

[0054] In the following, in conjunction with the examples, a polyamide material, a polyamide composite rubber seal and a preparation method thereof described in the present invention are further described in detail. For the sake of simplicity of description, this document cannot list all the alternative technical features and implementation schemes contained in the present invention. Therefore, those skilled in the art should know that any technical features and implementation schemes in this embodiment do not limit the scope of protection of the present invention, and the scope of protection includes any alternative technical features and implementation schemes adopted by all those skilled in the art without creative labor. Specifically, the implementation schemes obtained by replacing any technical feature in the present invention or combining any two or more technical features provided by the present invention should be within the scope of protection of the present invention. For those in the examples where specific techniques and conditions are not specified, the techniques and conditions described in the literature in the field or the product instructions are followed. The reagents or instruments used where the manufacturer is not specified are all conventional products that can be purchased commercially.

[0055] The present invention starts from the perspective of molecular structure construction, prepares polyamide materials, utilizes its excellent comprehensive properties (good flexibility, elongation at break, chemical corrosion resistance, excellent wear resistance, aging resistance, high and low temperature stability, deformation recovery and excellent interfacial activity, etc.), and coats and compounds it with traditional rubber to improve the friction performance of rubber seals. At the same time, compared with traditional rubber and plastic modification, its interfacial adhesion is greatly improved through its active tertiary amine group and the polar interface of the rubber after plasma treatment, and finally obtains a polyamide composite rubber seal product that is resistant to friction and shear and suitable for high-performance seals.

[0056] The present invention provides a method for preparing a polyamide material, comprising the following steps:

[0057] Step 1), preparation of trihalotriamide monomer:

[0058] S1, 100-105 parts of diethylenetriamine, 120-130 parts of alkali, and 0.5-20 parts of surfactant are sequentially added into 2500-5000 parts of deionized water, and dissolved at room temperature to obtain a diethylenetriamine solution;

[0059] S2, 475-660 parts of p-halobenzoyl halide and 3000-5000 parts of organic solvent are uniformly mixed, diethylenetriamine solution is added dropwise, and the mixture is reacted at room temperature for 2-5 hours to obtain a trihalotriamide monomer solution;

[0060] S3, distilling and recovering the organic solvent in the trihalotriamide monomer solution, collecting the crude product, washing, removing the solvent, and drying to obtain the purified trihalotriamide monomer.

[0061] Step 2), polyamide material preparation:

[0062] Q1, 10-300 parts of dihalogenated polyether diamide monomer, 0.5-20 parts of catalyst, 5-40 parts of dehydrating agent, 110-320 parts of aromatic diphenol, 80-300 parts of alkali and 1000-2000 parts of polar solvent are mixed evenly, and dehydrated at 130-190°C for 0.5-3h under nitrogen protection;

[0063] Q2, add 200-300 parts of dihaloamide monomer containing tertiary amine structure and 2-20 parts of trihalotriamide monomer obtained in step 1) to the solution obtained in the above Q1, react at 190-230° C. for 1-8 hours, and cool to 25-150° C. to obtain a polyamide material.

[0064] Further, in an embodiment of the present invention, the base used in the alkaline environment during the reaction of step 1) and step 2) is one of hydroxide, carbonate, and organic amine. It should be understood that the base that can be selected in step 1) includes but is not limited to one of sodium hydroxide, potassium hydroxide, lithium hydroxide, sodium carbonate, potassium carbonate, lithium carbonate, triethylamine, trimethylamine, and tripropylamine. In this embodiment, the base used in step 1) is specifically sodium hydroxide, lithium hydroxide, sodium carbonate, potassium carbonate, triethylamine, and tripropylamine. It should be understood that the base that can be selected in step 2) includes but is not limited to one of lithium hydroxide, sodium hydroxide, calcium hydroxide, potassium hydroxide, barium hydroxide, lithium carbonate, sodium carbonate, potassium carbonate, barium carbonate, lithium bicarbonate, sodium bicarbonate, potassium bicarbonate, calcium bicarbonate, barium bicarbonate, triethylamine, tripropylamine, and tri-tert-butylamine. In this embodiment, the base used in step 2) is specifically sodium carbonate, potassium carbonate, lithium hydroxide, potassium hydroxide, and triethylamine.

[0065] Further, in an embodiment of the present invention, the surfactant used in step 1) is one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, sodium benzene sulfonate, sodium alginate, polysorbate, dodecylphenol polyoxyethylene ether, sorbitan monooleate, and polyethylene glycol. In this embodiment, the surfactant used in step 1) is specifically sodium dodecylbenzene sulfonate, PEG-200, PEG-600, sodium benzene sulfonate, polysorbate, and sorbitan monooleate.

[0066] Further, in an embodiment of the present invention, the organic solvent used in step 1) is one of acetone, low-carbon alcohols, methyl chloride, ethyl chloride, carbon disulfide, and chlorinated aromatic hydrocarbons. It should be understood that the selectable organic solvents include, but are not limited to, acetone, ethanol, methanol, dichloromethane, chloroform, carbon tetrachloride, 1,2-dichloroethane, 1,1,2,2-tetrachloroethane, carbon disulfide, chlorobenzene, m-dichlorobenzene, and one of 1,2,4-trichlorobenzene. In this embodiment, the specifically selected organic solvents are chloroform, chlorobenzene, 1,2-dichloroethane, acetone, carbon tetrachloride, and 1,1,2,2-tetrachloroethane.

[0067] Further, in an embodiment of the present invention, the catalyst is an organic acid salt of lithium, sodium, potassium, or zinc metal ions, and the organic acid salt that can be selected is one or more of acetate, propionate, butyrate, caproate, tartrate, sorbate, lysine, cystine, citrate, aminocaproate, nitrilotriacetate, glycolate, gluconate, heptanoate, glycocholate, dioctylsuccinate, ethylenediaminetetramethylenephosphate, alginate, p-aminobenzenesulfonate, p-toluenesulfonate, and stearate. It should be understood that the embodiments of the present invention cannot exhaustively list the organic acid salts that the catalyst can select, and in this embodiment, the catalyst is specifically selected as sodium acetate, zinc tartrate, sodium dioctylsuccinate, potassium ethylenediaminetetramethylenephosphate, lithium glycocholate, and zinc p-aminobenzenesulfonate.

[0068] Further, in an embodiment of the present invention, the polar solvent in step 2) is a highly polar aprotic solvent containing oxygen, nitrogen, and sulfur, and can be selected from dimethylacetamide, N-methylpropionamide, hexamethylphosphoric triamide, N-methylcaprolactam, N,N-dimethylpropylene urea, N,N,N'N'-tetramethyl urea, 1,3-dimethyl-2-imidazolidinone, N-methylpyrrolidone, N-cyclohexylpyrrolidone, 2-pyrrolidonequinoline, isoquinoline, diphenyl sulfone, benzophenone, sulfolane, dimethyl sulfone, dimethyl sulfoxide, 2,4-dimethylsulfolane, N-phenylmorpholine, dimethyl phthalate, diethyl phthalate, 1-methyl-3-propylimidazolium bromide, 1-methyl-3-isopropylimidazolium bromide, and one of 1,3-dipropylimidazolium bromide. It should be understood that the embodiments of the present invention cannot list all polar solvents. In this embodiment, the polar solvent is specifically selected from N-cyclohexylpyrrolidone, N-methylpyrrolidone, 1,3-dimethyl-2-imidazolidinone, dimethyl sulfoxide, benzophenone, and diethyl phthalate.

[0069] The present invention also provides a method for preparing a polyamide composite rubber seal, comprising the following steps: step 1), surface treatment of semi-vulcanized rubber: the semi-vulcanized rubber is cleaned with ethanol before use, and then subjected to low-temperature plasma treatment; step 2), preparation of the polyamide composite rubber seal: any of the above-mentioned polyamide materials is evenly coated on the surface of the semi-vulcanized rubber by means of rotary coating, and phase conversion is carried out in a phase conversion agent. After the gel reaction is completed, the solvent is purified to remove the residual solvent and by-product salt, and the polyamide composite rubber seal is obtained by molding after drying.

[0070] Further, in the embodiment of the present invention, the low temperature plasma treatment time is 2-60s, the treatment power is 20-100w, the treatment temperature is 25-100°C, and the coating thickness is controlled to be 70-200μm. It should be understood that the low temperature plasma treatment time can be specifically selected as 60s, 30s, 20s, 10s, 35s, 45s, the treatment power can be specifically selected as 100W, 50W, 60W, 20W, 30W, 70W, the treatment temperature can be specifically selected as 100°C, 80°C, 60°C, 25°C, 40°C, 70°C, and the polyamide material coating thickness can be specifically 130μm, 150μm, 140μm, 160μm, 200μm, 70μm.

[0071] Further, in an embodiment of the present invention, during the molding process, the molding temperature is 100-280°C, the molding pressure is 1-10MPa, and the molding time is 2-30min. It should be understood that the molding temperature can be specifically selected as 160°C, 150°C, 168°C, 100°C, 280°C, 200°C, the molding pressure can be specifically selected as 3MPa, 2.5MPa, 3.5Mpa, 1MPa, 10MPa, 8Mpa, and the molding time can be specifically selected as 5min, 8min, 2min, 30min, 2min, 15min.

[0072] Example

[0073] Some of the monomers used in the following examples were obtained by the following methods:

[0074] Difluoropolyether diamide aromatic monomers containing alkyl carbons of different lengths were synthesized from the Journal of Polymer Materials Science and Engineering, Vol. 38, No. 11, November 2022, Synthesis and Properties of Semi-aromatic Polyamide Thermoplastic Elastomers with Different Carbon Chain Lengths. The chemical structure of the monomer is as follows:

[0075]

[0076] Where y is 2, 5 or 33.

[0077] The bis(4-fluorobenzamidopropyl)methylamine monomer is prepared from CN108774316B "Cationic polyarylether resin, separation membrane and preparation method thereof". The chemical structure of the monomer is as follows:

[0078]

[0079] 3,5-difluorobenzoyl-4-amino-N,N-dimethylaniline monomer, 3,5-difluorobenzoyl-N,N-dimethylpropylenediamine monomer, and 3,5-dichlorobenzoyl-N,N-dimethylethylenediamine monomer are prepared from CN112851931A "A Corrosion-Resistant Polyarylether Resin, Corrosion-Resistant Separation Membrane and Preparation Method thereof". Among them, the chemical structure of 3,5-difluorobenzoyl-4-amino-N,N-dimethylaniline monomer is as follows:

[0080]

[0081] The chemical structure of 3,5-difluorobenzoyl-N,N-dimethylpropylenediamine monomer is as follows:

[0082]

[0083] The chemical structure of 3,5-dichlorobenzoyl-N,N-dimethylethylenediamine monomer is as follows:

[0084]

[0085] Example 1

[0086] (1) Preparation of trifluorotriamide monomers:

[0087] First, 103g of diethylenetriamine, 120g of sodium hydroxide, and 3g of sodium dodecylbenzenesulfonate are added to 5000g of deionized water in sequence, and dissolved at room temperature to obtain a diethylenetriamine solution; then 475g of p-fluorobenzoyl chloride and 5000g of chloroform are mixed evenly and added to a container; then the diethylenetriamine solution is dripped into the container, and after the diethylenetriamine solution is dripped, the reaction is continued at room temperature for 2h to generate a trifluorotriamide monomer; the chloroform in the above monomer is distilled and recovered, the crude product is collected, and the purified trifluorotriamide monomer is obtained by washing, removing the solvent, and drying;

[0088] (2) Preparation of polyamide materials:

[0089] 225 g of a difluoropolyetheramide monomer containing 33 alkyl carbons, 0.5 g of sodium acetate, 40 g of toluene, 186 g of 4,4-dihydroxybiphenyl, 126 g of sodium carbonate and 2000 g of N-cyclohexylpyrrolidone were added into a reaction kettle, and dehydrated at 190° C. for 0.5 h under nitrogen protection; then 205 g of a bis(4-fluorobenzamidopropyl)methylamine monomer containing a tertiary amine structure and 2 g of a trifluorotriamide monomer obtained in step (1) were added, and the reaction was continued at 200° C. for 8 h, and the temperature was lowered to 25° C. to obtain a polyamide material, which was sealed for later use.

[0090] (3) Preparation of polyamide composite rubber seals:

[0091] Before using the semi-vulcanized rubber, it is first cleaned with ethanol and treated with low-temperature plasma, with a treatment time of 60 seconds, a treatment power of 100W, and a treatment temperature of 100°C; then the polyamide material obtained in the above step (2) is coated on the treated rubber surface, the coating thickness is controlled to be 130μm, and gel transformation is carried out in water, and finally the residual solvent and polymerization by-product salt are removed with water, and then molded after drying, with a molding temperature of 160°C, a molding pressure of 3MPa, and a molding time of 5min, to finally obtain a polyamide composite rubber seal.

[0092] The friction coefficient of the polyamide composite rubber seal was measured by a friction and wear tester (5400 reciprocating times) to be 0.48, which was reduced by about 0.27-0.32 compared with the pure nitrile rubber 0.75-0.8, and the wear volume Mv was 1.010×10 6 μm 3 , greatly improving the friction properties of rubber.

[0093] Example 2

[0094] (1) Preparation of trichlorotriamide monomer:

[0095] First, 103 g of diethylenetriamine, 126 g of lithium hydroxide, and 6 g of PEG-200 are sequentially added to 4000 g of deionized water, and dissolved at room temperature to obtain a diethylenetriamine solution; then 525 g of p-chlorobenzoyl chloride and 4000 g of chlorobenzene are mixed evenly and added to a container; then the diethylenetriamine solution is dripped into the container, and after the diethylenetriamine solution is dripped, the reaction is continued at room temperature for 5 hours to generate trichlorotriamide monomer; the chlorobenzene in the above monomer is distilled and recovered, the crude product is collected, and the purified trichlorotriamide monomer is obtained by washing, removing the solvent, and drying;

[0096] (2) Preparation of polyamide materials:

[0097] 40 g of a difluoropolyetheramide monomer containing 5 alkyl carbons, 10 g of zinc tartrate, 30 g of xylene, 110 g of hydroquinone, 200 g of potassium carbonate and 1500 g of N-methylpyrrolidone were added into a reaction kettle, and dehydrated at 185° C. for 2 h under nitrogen protection; 217 g of a 3,5-difluorobenzoyl-4-amino-N,N-dimethylaniline monomer containing a tertiary amine structure and 5 g of the trichlorotriamide monomer obtained in step (1) were added, and the reaction was continued at 200° C. for 6 h, and the temperature was lowered to 60° C. to obtain a polyamide material, which was sealed for later use;

[0098] (3) Preparation of polyamide composite rubber seals:

[0099] Before using the semi-vulcanized rubber, it is first cleaned with ethanol and treated with low-temperature plasma, with a treatment time of 30 seconds, a treatment power of 50W, and a treatment temperature of 80°C; then the polyamide material obtained in the above step (2) is coated on the treated rubber surface, and its coating thickness is controlled to be 150μm, and gel transformation is carried out in an ethanol solution, and finally, the residual solvent and polymerization by-product salt are removed with an ethanol aqueous solution, and then molded after drying, with a molding temperature of 150°C, a molding pressure of 2.5MPa, and a molding time of 8min, to finally obtain a polyamide composite rubber seal.

[0100] The friction coefficient of the polyamide composite rubber seal was measured by a friction and wear tester (5400 reciprocating times) to be 0.45, which was reduced by about 0.3-0.35 compared with the pure nitrile rubber 0.75-0.8, and the wear volume Mv was 1.001×10 6 μm 3 , greatly improving the friction properties of rubber.

[0101] Example 3

[0102] (1) Preparation of tribromotriamide monomers:

[0103] First, 103 g of diethylenetriamine, 300 g of sodium carbonate, and 10 g of PEG-600 are added to 3000 g of deionized water in sequence, and dissolved at room temperature to obtain a diethylenetriamine solution; then 658.5 g of p-bromobenzoyl chloride and 5000 g of 1,2-dichloroethane are mixed evenly and added to a container; then the diethylenetriamine solution is dripped into the container, and after the diethylenetriamine solution is dripped, the reaction is continued at room temperature for 4 hours to generate a tribromotriamide monomer; the 1,2-dichloroethane in the above monomer is distilled and recovered, the crude product is collected, and the purified tribromotriamide monomer is obtained by washing, removing the solvent, and drying;

[0104] (2) Preparation of polyamide materials:

[0105] 23 g of a difluoropolyetheramide monomer containing two alkyl carbons, 10 g of sodium dioctyl succinate, 30 g of toluene, 228 g of bisphenol A, 200 g of potassium carbonate and 1800 g of 1,3-dimethyl-2-imidazolidinone were added to a reaction kettle, and dehydrated at 185° C. for 2 h under nitrogen protection; 248 g of a tertiary amine-containing 3,5-difluorobenzoyl-N,N-dimethylpropylenediamine monomer and 6 g of the tribromotriamide monomer obtained in step (1) were added, and the reaction was continued at 220° C. for 6 h, and the temperature was lowered to 80° C. to obtain a polyamide material, which was sealed for later use;

[0106] (3) Preparation of polyamide composite rubber seals:

[0107] Before using the semi-vulcanized rubber, it is first cleaned with ethanol and treated with low-temperature plasma, the treatment time is 20 seconds, the treatment power is 60W, and the treatment temperature is 60°C; then the polyamide material obtained in the above step (2) is coated on the treated rubber surface, the coating thickness is controlled to be 140μm, and gel transformation is carried out in an ethanol aqueous solution, and finally the residual solvent and polymerization by-product salt are removed with an ethanol aqueous solution, and then molded after drying, the molding temperature is 168°C, the molding pressure is 3.5MPa, and the molding time is 2min, and finally a polyamide composite rubber seal is obtained.

[0108] The friction coefficient of the polyamide composite rubber seal was measured by a friction and wear tester (5400 reciprocating times) to be 0.51, which was reduced by about 0.23-0.29 compared with the pure nitrile rubber 0.75-0.8, and the wear volume Mv was 1.100×10 6 μm 3 , greatly improving the friction properties of rubber.

[0109] Example 4

[0110] (1) Preparation of trifluorotriamide monomer:

[0111] First, 100 g of diethylenetriamine, 120 g of potassium carbonate, and 0.5 g of sodium benzenesulfonate are sequentially added into 2500 g of deionized water, and dissolved at room temperature to obtain a diethylenetriamine solution; then 475 g of p-fluorobenzoyl chloride and 3000 g of acetone are mixed evenly and added into a container; then the diethylenetriamine solution is dripped into the container, and after the diethylenetriamine solution is dripped, the reaction is continued at room temperature for 2 hours to generate trifluorotriamide monomer; the acetone in the above monomer is distilled and recovered, the crude product is collected, and the purified trifluorotriamide monomer is obtained by washing, removing the solvent, and drying;

[0112] (2) Preparation of polyamide materials:

[0113] 300 g of a difluoropolyetheramide monomer containing 33 alkyl carbons, 0.5 g of potassium ethylenediaminetetramethylenephosphate, 40 g of toluene, 186 g of bisphenol S, 80 g of lithium hydroxide and 1000 g of dimethyl sulfoxide were added to a reaction kettle, and dehydrated for 0.5 h at 190° C. under nitrogen protection; 200 g of a tertiary amine structure-containing 3,5-difluorobenzoyl-N,N-dimethylethylenediamine monomer and 2 g of the trifluorotriamide monomer obtained in step (1) were added, and the reaction was continued at 230° C. for 8 h, and the temperature was lowered to 25° C. to obtain a polyamide material, which was sealed for later use;

[0114] (3) Preparation of polyamide composite rubber seals:

[0115] Before using the semi-vulcanized rubber, it is first cleaned with ethanol and treated with low-temperature plasma, the treatment time is 10s, the treatment power is 20w, and the treatment temperature is 25°C; then the polyamide material obtained in the above step (2) is coated on the treated rubber surface, the coating thickness is controlled to be 160μm, and gel transformation is carried out in water, and finally the residual solvent and polymerization by-product salt are removed by water, and then molded after drying, the molding temperature is 100°C, the molding pressure is 1MPa, and the molding time is 30min, and finally a polyamide composite rubber seal is obtained.

[0116] The friction coefficient of the polyamide composite rubber seal was measured by a friction and wear tester (5400 reciprocating times) to be 0.47, which was reduced by about 0.28-0.33 compared with the pure nitrile rubber 0.75-0.8, and the wear volume Mv was 1.000×10 6 μm 3 , greatly improving the friction properties of rubber.

[0117] Example 5

[0118] (1) Preparation of trichlorotriamide monomer:

[0119] First, 103g of diethylenetriamine, 125g of triethylamine, and 10g of polysorbate are sequentially added into 4000g of deionized water, and dissolved at room temperature to obtain a diethylenetriamine solution; then, 525g of p-chlorobenzoyl chloride and 4000g of carbon tetrachloride are evenly mixed and added into a container; then, the diethylenetriamine solution is dripped into the container, and after the diethylenetriamine solution is dripped, the reaction is continued at room temperature for 4h to generate trichlorotriamide monomer; the carbon tetrachloride in the above monomer is distilled and recovered, the crude product is collected, and the purified trichlorotriamide monomer is obtained by washing, removing the solvent, and drying;

[0120] (2) Preparation of polyamide materials:

[0121] 40 g of a difluoropolyetheramide monomer containing 5 alkyl carbons, 10 g of lithium glycocholate, 20 g of xylene, 110 g of resorcinol, 200 g of potassium hydroxide and 1500 g of benzophenone were added into a reaction kettle, and dehydrated at 170° C. for 1.5 h under nitrogen protection; 250 g of a 3,5-dichlorobenzoyl-N,N-dimethylethylenediamine monomer containing a tertiary amine structure and 10 g of the trichlorotriamide monomer obtained in step (1) were added, and the reaction was continued at 200° C. for 6 h, and the temperature was lowered to 60° C. to obtain a polyamide material, which was sealed for later use;

[0122] (3) Preparation of polyamide composite rubber seals:

[0123] Before using the semi-vulcanized rubber, it is first cleaned with ethanol and treated with low-temperature plasma, with the treatment time being 35 seconds, the treatment power being 30W, and the treatment temperature being 40°C; then the polyamide material obtained in the above step (2) is coated on the treated rubber surface, with the coating thickness being controlled to be 200 μm, and gel transformation is carried out in an ethanol solution, and finally the residual solvent and polymerization by-product salt are removed with an ethanol aqueous solution, and then molded after drying, with the molding temperature being 280°C, the molding pressure being 10 MPa, and the molding time being 2 minutes, to finally obtain a polyamide composite rubber seal.

[0124] The friction coefficient of the polyamide composite rubber seal was measured by a friction and wear tester (5400 reciprocating times) to be 0.43, which was reduced by about 0.32-0.37 compared with the pure nitrile rubber 0.75-0.8, and the wear volume Mv was 1.004×10 6 μm 3 , greatly improving the friction properties of rubber.

[0125] Example 6

[0126] (1) Preparation of tribromotriamide monomer:

[0127] First, 105g of diethylenetriamine, 130g of tripropylamine, and 20g of sorbitan monooleate are added to 5000g of deionized water in sequence, and dissolved at room temperature to obtain a diethylenetriamine solution; then 660g of p-bromobenzoyl chloride and 5000g of 1,1,2,2-tetrachloroethane are mixed evenly and added to a container; then the diethylenetriamine solution is dripped into the container, and after the diethylenetriamine solution is dripped, the reaction is continued at room temperature for 5 hours to generate a tribromotriamide monomer; 1,1,2,2-tetrachloroethane in the above monomers is distilled and recovered, the crude product is collected, and the purified tribromotriamide monomer is obtained by washing, removing the solvent, and drying;

[0128] (2) Preparation of polyamide materials:

[0129] 10 g of a difluoropolyetheramide monomer containing two alkyl carbons, 20 g of zinc p-aminobenzenesulfonate, 5 g of toluene, 320 g of 1,1'-bis(4-hydroxyphenyl)cyclohexane, 300 g of triethylamine and 2000 g of diethyl phthalate were added into a reaction kettle, and dehydrated for 0.5 h at 130° C. under nitrogen protection; 300 g of a tertiary amine structure-containing 3,5-dibromobenzoyl-N,N-dimethylethylenediamine monomer and 20 g of the tribromotriamide monomer obtained in step (1) were then added, and the reaction was continued at 190° C. for 1 h, and the temperature was lowered to 150° C. to obtain a polyamide material, which was sealed for standby use;

[0130] (3) Preparation of polyamide composite rubber seals:

[0131] Before using the semi-vulcanized rubber, it is first cleaned with ethanol and treated with low-temperature plasma, with the treatment time being 45 seconds, the treatment power being 70W, and the treatment temperature being 70°C; then the polyamide material obtained in the above step (2) is coated on the treated rubber surface, with the coating thickness being controlled to be 70 μm, and gel transformation is carried out in an ethanol aqueous solution, and finally the residual solvent and polymerization by-product salt are removed with an ethanol aqueous solution, and then molded after drying, with the molding temperature being 200°C, the molding pressure being 8MPa, and the molding time being 15min, to finally obtain a polyamide composite rubber seal.

[0132] The friction coefficient of the polyamide composite rubber seal was measured by a friction and wear tester (5400 reciprocating times) to be 0.52, which was about 0.23-0.28 less than that of pure nitrile rubber (0.75-0.8). The wear volume Mv was 1.100×10 6 μm 3 , greatly improving the friction properties of rubber.

[0133] Comparative Example

[0134] Comparative Example 1

[0135] The difference between the preparation method of a polyamide material and a polyamide composite rubber seal provided in Comparative Example 1 and that in Example 1 is that in Comparative Example 1, no bis(4-fluorobenzamidopropyl)methylamine monomer is added.

[0136] The polyamide composite rubber seal product obtained in Comparative Example 1 has a friction coefficient of 0.62 measured by a friction and wear tester (5400 reciprocating times), which is about 0.14 higher than that of the polyamide composite rubber seal product obtained in Example 1, and a wear volume Mv of 1.220×10 6 μm 3 .

[0137] Comparative Example 2

[0138] The difference between the preparation method of a polyamide material provided in Comparative Example 2 and that in Example 1 is that in Comparative Example 1, no carbon difluoropolyetheramide monomer containing 33 alkyl groups is added.

[0139] The friction coefficient of the polyamide composite rubber seal product obtained in Comparative Example 2 was 0.56 measured by a friction and wear tester (5400 reciprocating times), which was about 0.08 higher than that of the polyamide composite rubber seal product obtained in Example 1, and the wear volume Mv was 1.110×10 6 μm 3 .

[0140] Comparative Example 3

[0141] The difference between the preparation method of a polyamide material provided in Comparative Example 3 and that in Example 1 is that in Comparative Example 1, no trifluorotriamide monomer is added.

[0142] The polyamide composite rubber seal product obtained in Comparative Example 3 has a friction coefficient of 0.63 measured by a friction and wear tester (5400 reciprocating times), which is about 0.15 higher than that of the polyamide composite rubber seal product obtained in Example 1, and the wear volume Mv is 1.260×10 6 μm 3 .

[0143] For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived from them are still within the scope of protection of the claims of the invention.

Claims

1. A method for preparing a polyamide material, characterized in that: The steps include: Step 1), preparation of trihalotriamide monomer: The alkaline aqueous solution of diethylenetriamine is added dropwise to the organic solution of p-halobenzoyl halide to react, and the purified trihalotriamide monomer is obtained by distillation, washing and drying; Step 2), polyamide material preparation: The dihalogenated polyether diamide monomer and aromatic diphenol are subjected to a dehydration reaction in an alkaline polar solvent in the presence of a dehydrating agent and a catalyst; a dihalogenated amide monomer and a trihalogenated triamide monomer containing a tertiary amine structure are added to react with the temperature raised, and the temperature is lowered to obtain a polyamide material; Wherein, the dihalogenated polyether diamide monomer is: ; Where y is 2, 5 or 33; The dihaloamide monomer containing a tertiary amine structure is: 、 、 、 ; One of a kind.

2. The method for preparing a polyamide material according to claim 1, characterized in that: The trihalotriamide monomer is: ; The aromatic diphenol is: , , , , , , , , , One of; Wherein, X is F, Cl or Br.

3. The method for preparing a polyamide material according to claim 1, characterized in that: Step 1), preparation of trihalotriamide monomer, comprising the following steps: S1, 100-105 parts of diethylenetriamine, 120-130 parts of alkali, and 0.5-20 parts of surfactant are sequentially added into 2500-5000 parts of deionized water, and dissolved at room temperature to obtain a diethylenetriamine solution; S2, 475-660 parts of p-halobenzoyl halide and 3000-5000 parts of organic solvent are uniformly mixed, diethylenetriamine solution is added dropwise, and the mixture is reacted at room temperature for 2-5 hours to obtain a trihalotriamide monomer solution; S3, distilling and recovering the organic solvent in the trihalogenated triamide monomer solution, collecting the crude product, washing, removing the solvent, and drying to obtain a purified trihalogenated triamide monomer; Step 2), preparation of polyamide material, comprising the following steps: Q1, 10-300 parts of dihalogenated polyether diamide monomer, 0.5-20 parts of catalyst, 5-40 parts of dehydrating agent, 110-320 parts of aromatic diphenol, 80-300 parts of alkali and 1000-2000 parts of polar solvent are mixed evenly, and dehydrated at 130-190°C for 0.5-3h under nitrogen protection; Q2, add 200-300 parts of dihaloamide monomer containing tertiary amine structure and 2-20 parts of trihalotriamide monomer obtained in step 1) to the solution obtained in the above Q1, react at 190-230°C for 1-8h, and cool to 25-150°C to obtain polyamide material.

4. The method for preparing a polyamide material according to claim 3, characterized in that: In the step 1) of preparing the trihalotriamide monomer, the base is one of a hydroxide, a carbonate, and an organic amine; The surfactant is one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, sodium benzene sulfonate, sodium alginate, polysorbate, dodecylphenol polyoxyethylene ether, sorbitan monooleate, and polyethylene glycol; The organic solvent is one of acetone, low-carbon alcohols, methyl chloride, ethyl chloride, carbon disulfide, and chlorinated aromatic hydrocarbons.

5. The method for preparing a polyamide material according to claim 3, characterized in that: In the step 2) of preparing the polyamide material, the catalyst is an organic acid salt of lithium, sodium, potassium or zinc metal ions; The dehydrating agent is one of toluene and xylene; The base is one of hydroxide, carbonate and organic amine; The polar solvent is a highly polar aprotic solvent containing oxygen, nitrogen and sulfur.

6. A polyamide material, characterized in that: The polyamide material is prepared by the preparation method of any one of claims 1 to 5.

7. A method for preparing a polyamide composite rubber seal, characterized in that: The following steps are involved: Step 1), surface treatment of semi-vulcanized rubber: the semi-vulcanized rubber is cleaned with ethanol before use, and then treated with low-temperature plasma; Step 2), preparation of polyamide composite rubber sealing material: the polyamide material obtained by the preparation method of the polyamide material according to any one of claims 1 to 5 is evenly coated on the surface of the semi-vulcanized rubber by spin coating, and phase conversion is carried out in a phase conversion agent. After the gel reaction is completed, the solvent is purified to remove the residual solvent and by-product salt, and then molded after drying to obtain a polyamide composite rubber sealing member.

8. The method for preparing a polyamide composite rubber seal according to claim 7, characterized in that: The low temperature plasma treatment time is 2-60s, the treatment power is 20-100w, and the treatment temperature is 25-100°C; During the coating, the coating thickness is controlled to be 70-200 μm; The phase conversion agent is any one of deionized water, low-carbon alcohol aqueous solution, acetone aqueous solution, NMP aqueous solution, DMF aqueous solution, DMAc aqueous solution, and DMI aqueous solution; During the molding process, the molding temperature is 100-280°C, the molding pressure is 1-10MPa, and the molding time is 2-30min; The purification solvent is any one of deionized water and low-carbon alcohol.

9. A polyamide composite rubber seal, characterized in that: The polyamide composite rubber seal is prepared by the preparation method of any one of claims 7-8.